IMPLEMENTASI NATURAL LANGUAGE PROCESSING PADA CHATBOT UNTUK LAYANAN INFORMASI WISATA (STUDI KASUS: TANGERANG RAYA) - Hadinata, Wira; Stianingsih, Lilis (JURNAL ILMIAH INFORMATIKA, 2024)
The development of computer-based information technology is so fast that it has made many changes in human life. One of the latest technological developments that is becoming the center of attention is artificial intelligence. With this artificial intelligence, computers can perform certain tasks like humans do, namely chatting (chatbot). Chatbot is a computer program that can handle and respond to conversations through writing. The tourism sector is one area that has the potential to grow the economy of a region. Tourism is closely related to the use of information technology. Tourism in Greater Tangerang has the potential to be visited by many tourists. However, the development of existing tourism information is still considered to be less effective and informative. In conveying information, it is still done manually, namely from information heard by other people. Therefore, researchers are trying to develop a chatbot application as a helpdesk using a Natural Language Processing approach. With this application, tourists will be able to ask questions and answers to the system being built. This application uses language that is used daily for humans to communicate with each other.